The PPARgamma-activator rosiglitazone does not alter remodeling but increases mortality in rats post-myocardial infarction. - Lygate, C; Hulbert, K; Monfared, M; Cole, M; Clarke, K; Neubauer, S (2003)
OBJECTIVE: Peroxisome proliferator-activated receptor gamma (PPARgamma) activators may be beneficial in heart failure due to their metabolic and antihypertrophic effects, but these agents can cause oedema. We hypothesized that, on balance, the PPARgamma activator rosiglitazone would be beneficial in heart failure post-myocardial infarction. METHODS AND RESULTS: Rosiglitazone (3 mg/kg/day p.o.) given to male Wistar rats for 14 days, caused a 31% increase in left ventricular (LV) dP/dt(max) (P<0.05 vs. placebo). A separate group of rats was subjected to sham (SH) or coronary artery ligation and randomised to: untreated (UT); rosiglitazone 3 mg/kg/day (R); captopril, 2 g/l in drinking water (C); captopril+rosiglitazone (C+R). Mean LV infarct sizes were similar for all groups at 40+/-2%. After 8 weeks, echocardiographic ejection fractions were 82+/-3, 40+/-3, 50+/-2*, 49+/-2, 50+/-3% for SH, UT, R, C and C+R groups, respectively (*P<0.05 vs. UT). Captopril prevented LV dilatation, but rosiglitazone did not. In vivo hemodynamics showed that only UT had significantly elevated LV end-diastolic pressures and reduced +dP/dt(max), with R partially, and C and C+R almost completely preventing the increase in LVEDP. Captopril, but not rosiglitazone, significantly reduced LV hypertrophy [LV/bw; 1.97+/-0.09 (SH), 2.15+/-0.04 (UT), 2.10+/-0.05 (R), 1.81+/-0.04* (C), 1.88+/-0.07 (C+R); *(P<0.05 vs. UT)]. Rosiglitazone increased 8-week mortality, which was 26% for R and 19% for C+R compared with 0% for UT and C (P=0.03 vs. UT). CONCLUSIONS: Rosiglitazone did not modulate LV remodeling, but was associated with increased mortality post-myocardial infarction (MI) in rats. The mechanisms require further study, but these results caution against use of PPARgamma activators in post-MI heart failure in non-diabetics.